Peningkatan Keterampilan Menulis Fiksi Remaja melalui Pelatihan bagi Siswa SMPN 1 Muaro Jambi - Kartika Putri, Aprilia; Mestika Putra, Yoga; Fitriah, Siti; Triandana, Anggi; Amri, Ulil (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2025)
:  Fiction writing skills represent an important form of creative expression that contributes significantly to the development of youth literacy. However, some junior high school students still struggle to express their ideas in a structured and imaginative way through short stories. This community service activity aimed to improve the fiction writing skills of students at SMP Negeri 1 Muaro Jambi through a structured and practical short story writing training for teenagers. The implementation methods included interactive lectures, writing trainings, individual mentoring, and work evaluation sessions. The activity involved 15 students from grades VIII and IX who demonstrated an interest in fiction writing. The results showed an improvement in participants’ ability to develop plots, characters, and the use of figurative language in their short stories. This activity had a positive impact on strengthening the school’s literacy culture and encouraged the emergence of new interests in the field of teen fiction writing. Therefore, this fiction writing training can serve as a sustainable model for developing youth literacy at the junior high school level